Contribuições da semiótica discursiva para as práticas de letramento no ensino de língua portuguesa - Silvane Aparecida Gomes (2023)
This study is inserted around Applied Linguistics and is based on formative research in the teaching of Portuguese Language, addressing the integration between the theoretical-methodological perspective of Discursive Semiotics (Greimas and Courtés, 1979), active methodologies (Bacich, Moran, 2018) and educational literacies. The general objective was to investigate the contribution of the assumptions of Discursive Semiotics to the enrichment of literacy practices of Basic Education students, through a pedagogical intervention (Damiani et al, 2013), as an alternative to meeting the guidelines of semiotic analysis in Base National Common Curricular (BNCC, 2017). The analysis focused on three texts produced by Elementary School II students (9th year) from a peripheral public school in the city of Belo Horizonte/MG, based on the applied intervention, gathered in the book “Aquarelas Textuais”. The analyzes were portrayed, first, by the stages of the Content Analysis Theory (Bardin, 2016) and, by the Meaning Generative Path (Fiorin, 1995), as proposed by the Theory of Discursive Semiotics. The research proposes and establishes a reflection on teacher training, highlighting the importance of "training to train". In this context, I am based on the teaching practices of Portuguese language teachers (Pietri, 2010; Magalhães, 2010), with an emphasis on the use of Digital Information and Communication Technologies (TDIC) (Lévy, 1999; Kenski, 2003), and carry out a systematic review of the literature, exploring topics such as teaching proficiency and teaching choices. These approaches support the investigation of literacy in Portuguese, seeking to optimize this process. The research emphasizes the intersection between educational literacies, active methodologies, mobility and Discursive Semiotics, exploring concepts such as literacy at school (Kleiman, 1995; Soares, 2015), school literacy (Dering, 2021), digital literacy (Buzato, 2006, 2009; Santos, Lacerda, 2017), literacy from a decolonial perspective (Dering, 2021) and critical literacy (Street, 1984, 2014). This interrelationship results in the notion of the concept of integrated literacy, focusing on a proposal to enhance these literacies through the elements that constitute them, using mobile learning (Kukulska-Hulme 2009; Bottentuit Junior, 2012). The role of the internet as a mediator of teaching and learning in the Portuguese language stands out. The Semiotic perspective is introduced as a tool to facilitate learning and as a framework to support the development of reading skills (Pepulim et al, 2013; Pereira, 2019), proposing its association with the classroom context. The theoretical currents of Semiotics are presented, their relationship with linguistics and communication, and a brief approach to Discursive Semiotic theory is made. These elements integrate the production process and contextualize the semiotic analyzes and the different acts of research, such as the locus of the project, the research subjects, the technological devices in the field, the constitution of the research field and the epistemology of the method are described in detail. This information revealed three types of semiotic contexts of the specific object, classified as internal, external, and situational contexts (Barros, 2002). Based on these considerations, we sought to highlight the relevance of the strict use of semiotic concepts by teachers, opening new perspectives and possibilities to improve reading teaching practices during the work conducted with students, with the aim of promoting a production more proficient text. From a comprehensive and multidisciplinary perspective in the field of Portuguese language teaching, this thesis sought to elucidate how the integration of these educational resources can enrich pedagogical practice and improve learning processes, aiming to expand the scope of both teacher training and the development of citizen literacy. from the students.